New conception of 3×4 circularly polarized antenna patch network for RF energy harvesting at 2.45 GHz - Walid En-Naghma; Hanan Halaq; Abdelghani El Ougli (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper presents a developed design of a 3×4 circular polarization microstrip antenna patch array whose its resonance frequency is 2.45 GHz in the ISM band. This array is printed on a FR4 substrate of 1.58 mm thickness with a dielectric permittivity of 4.4. The basic antenna patch is a square shape inserted by a rectangular slot inclined positioned diagonally at the center to achieve circular polarization. In addition, a triangular-shaped slit is added at each of the four corners of the patch. The antenna array performance is tested numerically using two different software packages, CST MWS and HFSS. The antenna’s array size is compacted to a 22.7 cm×13.5 cm. The simulated results give good performance results in terms of return loss and gain; directivity is found to be 9.66 dBi at 2.45 GHz; the axial ratio value is 1.69 dB; and total efficiency is about 95.55% at 2.45 GHz. Then, the simulated results obtained by these two programs are in good agreement, which makes this proposed array design very suitable for radio frequency energy harvesting and its various applications to power supply different devices in a clean way for our environment.